EKSPLORASI IMPLEMENTASI KURIKULUM MERDEKA PADA TK NEGERI DAN SWASTA : STUDI KOMPARATIF DI SAMARINDA - Ayu Aprilia Pangestu Putri; Chandra Fauzi; Muhammad Ibnu Sa'ad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the implementation of the Merdeka Curriculum in formal Early Childhood Education (ECE) services, specifically in public and private kindergartens in Samarinda. A qualitative approach with a comparative case study design was employed. The primary data sources consisted of observation reports, photo and video documentation, and interviews with teachers and school principals. Data were analyzed through data reduction, data display, and conclusion drawing, strengthened by source triangulation. The findings indicate that both kindergartens have implemented the principles of the Merdeka Curriculum holistically. The dominant methods used were habituation and role modeling in fostering religious, moral, and character values. The results reveal that the public kindergarten applied a center-based learning approach (preparation, block, art, and nature centers), emphasizing interfaith tolerance and children's independence. In contrast, the private kindergarten explicitly integrated Islamic values into every learning theme and adopted a contextual STEAM approach. Assessment practices in both kindergartens were conducted authentically through daily observations, anecdotal records, checklists, and documentation of children's work. A significant difference was found in the assessment documentation system, where the private kindergarten demonstrated a more structured approach and a deeper integration of religious values in its implementation.